Solid supported microwave induced synthesis of imidazole–pyrimidine hybrids: Antimicrobial evaluation and docking study as 14DM-CPY51 inhibitors - Naziyanaz B. Pathan; Anjali M. Rahatgaonkar (Arabian Journal of Chemistry, 2016)
As part of our exploration for new antifungal agents, substituted 4,5-diphenyl imidazolyl pyrimidine hybrids were synthesized. A series of substituted ethyl 1,2,3,6-tetrahydro-4-methyl-2-oxo/thioxo-6-phenyl-1-(4,5-diphenyl-1-H-imidazol-2-yl) pyrimidine-5-carboxylates have been studied for their binding active sites of cytochrome P450 14α-sterol demethylase CPY51 enzyme. For comparison, the binding behavior of known 14DM selective (Fluconazole) and non-selective (Clotrimazole, Miconazole, Griesofulvin) drugs has also been studied. Synthesized compounds were screened for their in vitro antibacterial activity against Staphylococcus aureus, Salmonella typhi, Pseudomonas aurogenosa and Klebsiella pneumonae and also antifungal activity against the opportunistic pathogens Candida albicans.